Assessment of Short- and Long-Term Outcomes of Patients Hospitalized With Intracerebral Hemorrhage - Lin, Chih-Ming; Feng, Wayne (Current Neurovascular Research, 2012)
The aim of this study was to assess short- and long-term outcomes of patients hospitalized with intracerebral hemorrhage (ICH) in South Carolina. Patients with a primary diagnosis of ICH (ICD-9-CM code 431) discharged during 2002 were identified in the South Carolina hospital discharge database. Kaplan-Meier estimates of recurrent stroke, myocardial infarct, vascular death, all-cause death, and composite events were calculated at 1 month, 6 months, and 1, 2, 3, and 4 years. Age- and race-specific survival curves were plotted. A total of 893 patients were discharged during 2002. Most were Caucasian (CA) (61.4%), followed by African American (AA) (37.4%). The mean age of patients in the AA group was 12 years younger than that of the CA group; of those in the AA group, 63.8% were <65 years of age, and of those in the CA group, 27.4% were >65 years of age. Kaplan-Meier estimates of cumulative risk increased with time over the 4-year period after discharge, and the risk of all-cause death was high (∼40%-60%). Survival curves showed that the composite risk of recurrent stroke, myocardial infarct, or vascular death was higher for AA patients <65 years of age compared to similarly aged CA patients, whereas the risk was higher for CA patients >65 years of age compared to similar age AA patients. The racial disparity in short- and long-term outcomes for ICH patients <65 years of age in South Carolina highlights the need for improvements in stroke prevention, particularly among the AA population.
Keywords: ICH